Taxonomia das espécies do grupo oiketicusi de Conura (Chalcididae, Hymenoptera) - Saguiah, Pâmella Machado (2015)
A Review of the species of oiketicusi group Conura (Chalcididae, Hymenoptera) is presented. The group was proposed by Delvare (1992) and until the moment meets six species [Conura basilica (Walker, 1864), C. elaeisis Delvare, 1993, C. fortidens (Cameron, 1909), C. giraulti De Santis, 1979, C. mexicana (Cresson, 1872) and C. oiketicusi (Cameron, 1913)]. At least some of the species are parasitoids of Oiketicus sp. (Psychidae, Lepidoptera) and only their original descriptions treat their morphological characteristics, these being insufficient to properly identify the species. Therefore, most species is not can be recognized using the literature. A series of four types nominal species were analyzed. The following synonyms are proposed: C. elaeisis and C. oiketicusi as synonyms junior C. basilica. Redescriptions are presented for C. basilica, C. fortidens and C. giraulti. Considerations were made for C. mexicana and a species not determined is treated here.